Interrelationships of warthogs (Phacochoerus africanus), Ornithodoros ticks and African swine fever virus in South Africa - Swanepoel, Robert (University of Pretoria, 2023)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2022.